CHARACTERIZATION OF NEONATAL DEATHS FROM HEALTHCARE-RELATED INFECTIONS IN A MATERNITY SCHOOL - Clara Tavares Rangel; Nilba Lima de Souza; Cecília Olívia Paraguai de Oliveira (Universidade Federal do Paraná, 2012)
This study aimed to characterize the neonatal deaths from infection related to health care provided in a neonatal intensive care unit in a maternity school, in the period August 2008 - June 2011. The data was analyzed using descriptive statistics with frequency of the variables. Greater mortality was recorded in male neonates, with low birth weights, lower Apgar scores, born via caesarian section and with a gestational age of below 37 weeks. The extrinsic factors were related to greater lengths of time spent hospitalized and exposed to invasive procedures. The neonates' birth conditions and the care interventions favored the appearance of infection and, consequently, the deaths, pointing to the need for preventive steps which would minimize avoidable risk factors for neonatal mortality, as a positive response to the service and to society.